2019
DOI: 10.1242/bio.047829
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous beta-catenin activation is sufficient to cause hepatocellular carcinoma in zebrafish

Abstract: Up to 41% of hepatocellular carcinomas (HCCs) result from activating mutations in the CTNNB1 gene encoding β-catenin. HCC-associated CTNNB1 mutations stabilize the β-catenin protein, leading to nuclear and/or cytoplasmic localization of β-catenin and downstream activation of Wnt target genes. In patient HCC samples, β-catenin nuclear and cytoplasmic localization are typically patchy, even among HCC with highly active CTNNB1 mutations. The functional and clinical relevance of this heterogeneity in β-catenin act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 70 publications
(111 reference statements)
1
15
0
Order By: Relevance
“…Up to 40% of human HCCs result from activating mutations in the gene encoding for β-catenin (CTNNB1). The zebrafish model was used to prove that activated β-catenin expression in a small subset of hepatocytes is sufficient to drive HCC initiation [209]. Zebrafish are effective as disease models because of their high fecundity, low housing cost, and transparency, which allows live imaging and is useful to explore mechanisms by which HBV and HCV induce HCC.…”
Section: Zebrafishmentioning
confidence: 99%
“…Up to 40% of human HCCs result from activating mutations in the gene encoding for β-catenin (CTNNB1). The zebrafish model was used to prove that activated β-catenin expression in a small subset of hepatocytes is sufficient to drive HCC initiation [209]. Zebrafish are effective as disease models because of their high fecundity, low housing cost, and transparency, which allows live imaging and is useful to explore mechanisms by which HBV and HCV induce HCC.…”
Section: Zebrafishmentioning
confidence: 99%
“…Additionally, the large number of CreER T2 expressing lines [ 224 ] offers a strong potential in terms of generation of zebrafish cancer models. However, only few applications of the conditional CreER T2 technology have been reported so far in the field of cancer modelling [ 225 , 226 ]. Kalasekar et al [ 225 ] generated a model of hepatocellular carcinoma based on the CreER T2 -mediated conditional expression of an activated version of β-catenin (Xla.Ctnnb1 S33A, S37A, T41A, S45A , and hereafter-named Ctnnb1 ACT ).…”
Section: Transgenesismentioning
confidence: 99%
“…However, only few applications of the conditional CreER T2 technology have been reported so far in the field of cancer modelling [ 225 , 226 ]. Kalasekar et al [ 225 ] generated a model of hepatocellular carcinoma based on the CreER T2 -mediated conditional expression of an activated version of β-catenin (Xla.Ctnnb1 S33A, S37A, T41A, S45A , and hereafter-named Ctnnb1 ACT ). In this system, a Tg(fapb10a:CreER T2 ) line expressing Cre recombinase fused to the modified LBD of the estrogen receptor downstream of the hepatocyte-specific fabp10a promoter is used as a driver line, whereas a Tg(fapb10a:loxP-BFP-loxP-Ctnnb1 ACT ) transgenic line serves as a switch target line.…”
Section: Transgenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, liver-specific expression of oncogenic kras V12 can drive robust liver tumorigenesis in transgenic zebrafish [ 33 ]. A recent study also indicated that heterogeneous β-catenin activation is sufficient to cause HCC in zebrafish [ 34 ]. Another study reported that gankyrin transgenic zebrafish spontaneously developed persistent hepatocyte damage, steatosis, cholestasis, cholangitis, fibrosis, and hepatic tumours at 7–12 months of age [ 35 ].…”
Section: Introductionmentioning
confidence: 99%